Exploring the Employability Factors of the Arts Undergraduates (Case from University of Sri Jayewardenepura) - Udaya Kumari, H.K.S.H.; Weerasena, U.M. (IRCHSS-2018 and Faculty of Humanities and Social Sciences, University of Sri Jayewardenepura, 2018)
The demand for higher education in Sri Lanka is rapidly increasing. Yet Sri Lanka fails to get the labour force of the graduates who pass out of universities involved in the country’s development. Most of the job seekers’ desire is to get high paid employments with less skills. Among all the graduates, graduates of Arts faculties face much difficulties in the job market in finding a suitable employment. Though many students enroll for Arts faculties, one of the main problems face by them is not having a direct job after the graduation. Therefore, in deciding the future career path, it is very much vital to focus on other factors. The main purpose of this research is to identify the potentials of the undergraduates that affects for their future careers. For the research, a sample of 100 undergraduates was selected from the faculty of Humanities and Social Sciences using an equal proportion of stratified random sampling method. A structured questionnaire was used in collecting primary data. In analyzing the data, descriptive statistics and a factor analysis was performed to identify the potential factors and the identified factors affect to the employability of the undergraduates are personality, mentality, language proficiency and computer literacy. In conforming to the analysis, 81% of the respondents are more inclined towards the state sector and out of that, 41% of the respondents prefer to engage in teaching career. 23%, 12% and 4% of the respondents are more likely to do a job in administration sector, banking and consultation sector and mass media sector respectively. As per the factor analysis, it was discovered that there are four main factors which affects in determining future careers. It was examined that the most influential factor is the personality factor as it takes the largest value for “lamda” among other factors and it represents 37.2% of the total sample proportion. The second factor is mentality. Language proficiency and computer literacy takes third and fourth factors respectively. Therefore, it can be concluded that undergraduates should focus on their studies as well as the above potential factors if they are willing to be a demanded employee.
Keywords: ability; Arts degree; employability; undergraduate